Australian Poltergeist: The Stone-Throwing Spook of Humpty Doo and Many Other Cases by Tony Healy and Paul Cropper - Braude, Stephen (Journal of Scientific Exploration, 2015)
No doubt this breezily written and informative volume will fill a gaping lacuna in most JSE readers' knowledge of evidence for psychokinesis generally and poltergeist phenomena in particular. It certainly did for me. Healy and Cropper survey 52 different Australian cases, spanning the years 1845-2002. The first eleven chapters cover the authors' 11 strongest cases in considerable detail. Chapter 12 describes the remaining 41 cases more briefly, and catalogues all 52 cases in chronological order. Chapter 13 purports to wrap things up, but it's followed by three appendices introducing additional cases outside Australia and brief discussions of similar or at least potentially relevant physical mysteries-for example, some Asian fire poltergeist cases, ball lightning, UFOs, and reported rains of fishes. The authors rate their cases on a five-star scale, which they apply judiciously. Ratings begin at zero for apparent or proven hoaxes, and then range from half a star ("for questionable or very poorly documented cases" [p. 7]) to five stars. Healy and Cropper write: "With only two exceptions, we have reserved the four and five-star rating for very well documented cases where we were able to interview the eyewitnesses or in which we had some other personal involvement" (p. 7). The case they consider the strongest-the Mayanup case from 1955-2002-is the only one to earn five stars. Humpty Doo (1998)-possibly the most famous, or notorious-gets four and a half. Several cases earned between three and four stars, and quite a few get either zero stars or half a star. The two highest-rated cases are genuinely interesting. In the Humpty Doo case, many credible observers witnessed the phenomena under conditions which quite clearly seemed to rule out chicanery, and which conformed to poltergeist reports in other parts of the world. The phenomena included "showers of stones both indoors and out, dangerous objects thrown with great force but without causing injury, objects falling unnaturally slowly yet producing unnaturally loud sounds on impact, objects observed levitating, objects observed materializing in mid-air" (p. 48), the intense heat of apported objects, and more.